1968
DOI: 10.1152/ajplegacy.1968.215.4.857
|View full text |Cite
|
Sign up to set email alerts
|

Changes in distribution of cardiac output after hemorrhage in rabbits

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…Forsyth et al (29,30) have documented the pattern of regional blood flow and resistance associated with the activation of sympathetic nervous system by hemorrhage or hypothalamic stimulation in monkeys. Their results are consistent with results in other species and man (31)(32)(33)(34). This sympathetic reflex-mediated pattern demonstrates preservation of blood flow to the heart, brain, liver, and lung at the expense of less vital structures such as skin, bone, muscle, and abdominal viscera.…”
Section: Discussionsupporting
confidence: 90%
“…Forsyth et al (29,30) have documented the pattern of regional blood flow and resistance associated with the activation of sympathetic nervous system by hemorrhage or hypothalamic stimulation in monkeys. Their results are consistent with results in other species and man (31)(32)(33)(34). This sympathetic reflex-mediated pattern demonstrates preservation of blood flow to the heart, brain, liver, and lung at the expense of less vital structures such as skin, bone, muscle, and abdominal viscera.…”
Section: Discussionsupporting
confidence: 90%
“…21,22 This preferential redistribution of the cardiac output occurs at the expense of other vascular beds like the gut. 23 With continued peripheral circulatory insufficiency, tissue hypoperfusion becomes self-destructive as blood flow falls below the metabolic needs of the parenchymal cells and vital organs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, canine cutaneous blood flow was augmented in accordance with a blood pressure elevation evoked by the carotid reflex (BOND and GREEN, 1969), but on this occasion no constriction of the cutaneous vessels was obtained. In hemorrhaging, however, constriction of cutaneous vessels was observed (NEUTZE et al, 1968 ;FORSYTH et al, 1970;SCHWINGHAMER et al, 1970). IRIKI et al (1971) reported an augmentation of cutaneous and visceral sympathetic activity in a severe hypoxia.…”
Section: Discussionmentioning
confidence: 99%